Look at that building! : a first book of structures - Ritchie, Scot. (Toronto : Kids Can Press, 2011)
An engaging introduction to buildings, with a deft mix of nonfiction and fiction elements.
Includes index.
Booklist, September 2011.
Booklist.
1.6
K-3
Keywords: Building -- Juvenile literature; Building; Building; Buildings; Picture books for children